A conceptual research: The regulatory role of peer-to-peer engagement behaviors. (April 2022) - Lin, Meizhen; Miao, Li; Wei, Wei; Moon, Hyoungeun
Abstract: The growth of peer-to-peer businesses has seen the concomitant emergence of regulatory issues. Despite intensified regulatory efforts at multiple levels to address these issues, peer-to-peer markets continue to challenge regulators. Using cybernetic control theory as a theoretical framework, this conceptual paper systematically explores the regulatory function of peer engagement behaviors in the peer-to-peer business model. The paper discusses key regulatory functions driven by peer engagement behaviors, such as input, reference value, comparator and output. Corresponding propositions are offered. This paper also identifies critical issues related to the regulatory function of peer engagement behaviors and outlines future research directions on the topic. Graphical Abstract: ga1 Highlights: A peer-to-peer system can be regarded as a self-regulatory cybernetic system. Peerization and reciprocity of peer reviews strengthen peer engagement behaviors' regulatory role. Shared rulemaking and peer norms serve as reference values while collective vigilance serves as a comparator. Discrepancy output function manifests through approach and avoidance regulation.